Exploring the mechanism of Qingre Yishen Xiaozheng formula in treating diabetic kidney disease via the HIF-1α/HO-1 signaling pathway: an integrated network pharmacology and experimental study - Han, Fei; Shou, Jieyu; Wang, Yaoxian; Tian, Zhejing; Zheng, Huijuan; Liu, Lanying; Liu, Weijing (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceThe Qingre Yishen Xiaozheng Formula (QRYSXZF) is a traditional Chinese medicine prescription developed based on the “clearing heat and resolving stasis” principle, clinically applied for the treatment of diabetic kidney disease (DKD).Aim of the studyTo investigate the therapeutic effects of QRYSXZF on DKD and elucidate its underlying mechanisms through integrated network pharmacology and experimental validation, focusing on the HIF-1α/HO-1 signaling pathway and ferroptosis regulation.Materials and methodsActive components of QRYSXZF were screened using the TCMSP database (OB ≥ 30%, DL ≥ 0.18), and a herb-compound-target network was constructed via Cytoscape 3.8.0. DKD-related targets were retrieved from GeneCards, OMIM, and TTD databases. Protein-protein interaction (PPI) networks, GO/KEGG enrichment analyses, and molecular docking (PyMOL/AutoDock) were performed to predict core targets and pathways. In vivo, a DKD rat model was established by unilateral nephrectomy combined with streptozotocin (STZ) injection, followed by 12-week QRYSXZF treatment. Renal function markers (BUN, 24h-UTP, KIM-1, NGAL), oxidative stress (SOD, MDA, GSH-Px), iron metabolism (SI, SF, TF), and ferroptosis-related proteins (GPX4, ACSL4, FTH1, NCOA4) were analyzed. Histopathological changes were assessed by H&E, PAS, and Masson staining, while HIF-1α/HO-1 pathway activity was evaluated via Western blot.ResultsNetwork pharmacology identified 153 shared targets between QRYSXZF and DKD, with quercetin, kaempferol, and β-sitosterol as core active components, while KEGG analysis highlighted the HIF-1 signaling pathway as a key mechanism. In DKD rats, QRYSXZF significantly improved renal function by reducing BUN, Cys-C, KIM-1 and NGAL, attenuated oxidative stress through increasing SOD/GSH-Px and decreasing MDA, regulated iron metabolism by lowering SF and elevating TF, suppressed ferroptosis via upregulating GPX4/FTH1 and downregulating ACSL4/NCOA4, and inhibited HIF-1α/HO-1 pathway activation, with molecular docking confirming stable binding between QRYSXZF components and HIF1A/HMOX1.ConclusionQRYSXZF alleviates DKD progression by modulating the HIF-1α/HO-1 pathway to reduce ferroptosis, oxidative stress, and iron overload, providing a scientific basis for its clinical application in DKD management.